WAC loss-of-function mutations cause a recognisable syndrome characterised by dysmorphic features, developmental delay and hypotonia and recapitulate 10p11.23 microdeletion syndrome. Issue 11 (11th August 2015) - DeSanto, Cori; D'Aco, Kristin; Araujo, Gabriel C; Shannon, Nora; Study, DDD; Vernon, Hilary; Rahrig, April; Monaghan, Kristin G; Niu, Zhiyv; Vitazka, Patrik; Dodd, Jonathan; Tang, Sha; et al.
Abstract : Background: Rare de novo mutations have been implicated as a significant cause of idiopathic intellectual disability. Large deletions encompassing 10p11.23 have been implicated in developmental delay, behavioural abnormalities and dysmorphic features, but the genotype–phenotype correlation was not delineated. Mutations in WAC have been recently reported in large screening cohorts of patients with intellectual disability or autism, but no full phenotypic characterisation was described. Methods: Clinical and molecular characterisation of six patients with loss-of-function WAC mutations identified by whole exome sequencing was performed. Clinical data were obtained by retrospective chart review, parental interviews, direct patient interaction and formal neuropsychological evaluation. Results: Five heterozygous de novo WAC mutations were identified in six patients. Three of the mutations were nonsense, and two were frameshift; all are predicted to cause loss of function either through nonsense-mediated mRNA decay or protein truncation. Clinical findings included developmental delay (6/6), hypotonia (6/6), behavioural problems (5/6), eye abnormalities (5/6), constipation (5/6), feeding difficulties (4/6), seizures (2/6) and sleep problems (2/6). All patients exhibited common dysmorphic features, including broad/prominent forehead, synophrys and/or bushy eyebrows, depressed nasal bridge and bulbous nasal tip. Posteriorly rotated ears, hirsutism, deep-set eyes, thin upper lip, inverted nipples, hearing loss and branchial cleft anomalies were also noted. Conclusions: Our case series show that loss-of-function mutations in WAC cause a recognisable genetic syndrome characterised by a neurocognitive phenotype and facial dysmorphism. Our data highly suggest that WAC haploinsufficiency is responsible for most of the phenotypic features associated with deletions encompassing 10p11.23.